Compact Oxford English Dictionary of Current English (Oxford Oxford UP, 2003)
This revised second edition of the "Compact Oxford English Dictionary of Current English" offers up-to-the-minute coverage of over 145,000 words, phrases, and definitions from everyday English, including up-to-the-minute words, and in-text notes giving guidance on spelling, grammar, and usage.
Keywords: compact_dictionary; current_english; dictionary